Scale-bearing beauty: Intertidal scale-worms (Polychaeta: Polynoidae) from Punta Blanca (Arequipa, Peru) - Valencia-Soto, David (Zootaxa, 2021)
Three species of polynoid polychaetes were collected during an exploratory sampling on the rocky shore of Punta Blanca in Arequipa, Peru. Lepidonotus aff. crosslandi peruana Hartmann-Schröder, 1962 differed from the nominal species by the presence of jaws without denticles and bidentate neurochaetae in the third parapodium while Harmothoe aff. hirsuta Johnson, 1897, differed by a disparate distribution of elytral ornamentations. Halosydna parva Kinberg, 1856 is newly recorded for the locality. Comparative tables between Lepidonotus, Halosydna and Harmothoe species recorded for Peru and the Pacific Coast of South America are provided.